2003
DOI: 10.1098/rspb.2002.2326
|View full text |Cite
|
Sign up to set email alerts
|

Forest management is associated with physiological stress in an old–growth forest passerine

Abstract: We investigated how physiological stress in an area-sensitive old-growth forest passerine, the Eurasian treecreeper (Certhia familiaris), is associated with forest fragmentation and forest structure. We found evidence that the concentrations of plasma corticosterone in chicks were higher under poor food supply in dense, young forests than in sparse, old forests. In addition, nestlings in large forest patches had lower corticosterone levels and a better body condition than in small forest patches. In general, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
116
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 18 publications
(23 reference statements)
7
116
1
Order By: Relevance
“…Studies have shown that different species may cope differently with forest fragmentation and selective logging (Leshyk et al., 2012; Lucas et al., 2006; Mastromonaco et al., 2014; Suorsa et al., 2003, 2004; Wasser et al., 1997). Thus, we highlight that not all species may have predictable and similar physiological responses to forest disturbances (as suggested by Rimbach et al., 2013), even when consequences in relative abundance are negative for most of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that different species may cope differently with forest fragmentation and selective logging (Leshyk et al., 2012; Lucas et al., 2006; Mastromonaco et al., 2014; Suorsa et al., 2003, 2004; Wasser et al., 1997). Thus, we highlight that not all species may have predictable and similar physiological responses to forest disturbances (as suggested by Rimbach et al., 2013), even when consequences in relative abundance are negative for most of them.…”
Section: Discussionmentioning
confidence: 99%
“…For example, body fat content has been frequently used as a physiological biomarker to assess sublethal effects of many environmental stressors on vertebrates (Lucas et al., 2006; Suorsa et al., 2003, 2004) and insects (Irschick et al., 2013; Piiroinen et al., 2014; Reaney & Knell, 2015). Overall, such studies have shown that organisms under stressful conditions exhibit changes in the fat storage (Baldal et al., 2005; Piiroinen et al., 2014), which is suggested as a strategy to increase life span as a result of improved energy consumption efficiency (Broughton et al., 2005; Hansen, Flatt, & Aguilaniu, 2013) and to improve the starvation stress resistance (Arrese & Soulages, 2010; Lee & Jang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These corticosterone levels (mean + s.d. ¼ 31.2 + 12.0 ng ml 21 , min ¼ 10.1, max ¼ 81.1) were corrected for autolysis (Suorsa et al 2003a) by using studentized residuals from the regression of corticosterone on the total handling time of plasma (from bleeding to storing of plasma) as estimates of nestling corticosterone levels. The extracted blood cells of the same samples were also used for nestling sex determination applying DNA molecular methods (Suorsa et al 2003b).…”
Section: Methodsmentioning
confidence: 99%
“…During the summer of 2000, 9 day old nestlings (n ¼ 165) were blood sampled for 50-80 ml after a puncture of a tarsometatarsal vein (Suorsa et al 2003a), to measure plasma corticosterone levels using four radioimmunoassay kits (Biotrak rat corticosterone ( 125 I); Amersham, UK). The amount of blood sampled from nestlings did not allow us to determine the inter-and intra-assay coefficient of variation (CV) for the kits used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation